Twin-Twin Transfusion Syndrome After Radiofrequency Ablation in Dizygotic Monochorionic Triamniotic Triplet Pregnancy With Sex Discordance: A Case Report - Tang, Mingming; Tian, Xingbo; Luo, Jianglai; Zhang, Xiaohang; Ran, Suzhen; Xiong, Jiaojiao; Chen, Yanlin; Chen, Gongli (Frontiers in Medicine, 2022)
Background We report a case of dizygotic monochorionic triamniotic triplet pregnancy. Twin-twin transfusion syndrome was subsequently diagnosed combined with sex discordance in the two surviving fetuses after one fetus was reduced, which is extremely rare and has not been previously reported. Case Presentation After reducing one fetus by radiofrequency ablation of a monochorionic triamniotic triplet pregnancy, twin-twin transfusion syndrome was subsequently diagnosed combined with sex discordance in the two surviving fetuses. Amniotic fluid for chromosome analysis showed normal karyotype 46, XY/46, XX of the donor and recipient fetus, and short tandem repeat (STR) analysis revealed dizygotic twins. Conclusions Through this is an unusual case, we aim to emphasize the importance of accurate diagnosis of chorionicity and zygosity in sex discordant triplet pregnancy, which is the key to appropriate clinical management.